Mutually exclusive expression of alternatively spliced FMRFamide transcripts in identified neuronal systems of the snail Lymnaea - Bright, K (J Neurosci, 1993)
The FMRFamide gene of the snail Lymnaea encodes tetrapeptides (FMRFamide/FLRFamide) and heptapeptides (GDPFLRFamide/SDPFLRFamide) on separate exons. In situ hybridization probes specific to these exons were used to map the expression of the two exons in identified neuronal systems of the CNS. Analysis of more than 200 preparations showed that cytoplasmic expression of mRNA was exclusively of one type, with individual neurons expressing either the tetrapeptide or heptapeptide exon. Of the approximately 340 neurons expressing the two exons, the majority (80%) expressed the tetrapeptide exon. The tetrapeptide exon was more widespread, occurring in neurons from all 11 ganglia of the CNS. The heptapeptide was mainly confined to two ganglia (visceral and right parietal), with a small number of cells in three other ganglia. Mapping studies combined with dye marking of identified neurons showed the presence of the tetrapeptide exon in several behaviorally important networks: heart motoneurons, whole body withdrawal response motoneurons, and probably penis motoneurons as well as giant identified neurons (LP1, RPD1). The heptapeptides were prominent in two main clusters of cells (Bgp and Fgp) together with a smaller number of tetrapeptide-expressing cells.